ANALYSIS OF THE ALLELIC VARIATION OF THE VRN-1 AND PPD-1 GENES IN SIBERIAN EARLY AND MEDIUM EARLY VARIETIES OF SPRING WHEAT - I. E. Likhenko (Vavilovskij Žurnal Genetiki i Selekcii, 2015)
Combinations of alleles of the Vrn-A1, Vrn-B1, Vrn-D1, Ppd-D1, and Ppd-B1 genes were analyzed with allele-specific primers in 48 spring wheat varieties from different breeding centers in Siberia. Six haplotypes were identified for Vrn-1 genes, including two most abundant with two dominant genes Vrn-A1 and Vrn-B1 against the background of recessive Ppd-D1b genes, which cause sensitivity to photoperiod. Only one variety (Tulun 15) was found to bear the photoperiod-neutral Ppd-D1a allele, combined with the dominant Vrn-A1 and Vrn-B1 alleles. It showed the earliest ripening of all accessions examined. Within each haplotype, a considerable variability was found in growing duration, suggesting a strong influence of the “genetic background” on this trait. Nevertheless, the results can be used for marker-assisted selection of genotypes most appropriate for different growing conditions.